Telenursing’s Effectiveness on Mothers’s Ability to Stimulate Child Development - Atikah Fatmawati; Mujiadi Mujiadi; Anndy Prastya (Universitas Pendidikan Indonesia, 2022)
ABSTRACTIntroduction: Children have a golden period of development. The proper stimulation will stimulate the child's brain so that development can take place optimally according to age. Objective: This study aims to determine the effect of telenursing on the mother's ability to stimulate the development of children aged 9-12 months. Method: The study used a pre-experimental design with a pre-posttest one-group design approach. Thirty-two respondents were selected purposively. The telenursing intervention was given three times for one week using Whatsapp group media. The instrument used was the Stimulation Early Intervention Detection Growth and Development checklist. Result: Paired T-test results showed that telenursing effectively increased the mother's ability to stimulate growth and development in children (p=0.000). Telenursing allows nurses to control the delivery of nursing interventions, even if they do not meet in person. Conclusion: Telenursing can be an alternative method to provide nursing care, one of which is providing information about child development.ABSTRAKPendahuluan: Anak memiliki periode emas dalam masa perkembangan. Stimulasi yang tepat akan merangsang otak anak sehingga perkembangan dapat berlangsung optimal sesuai dengan usia. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh telenursing terhadap kemampuan ibu dalam melakukan stimulasi perkembangan anak usia 9-12 bulan. Metode: Penelitian menggunakan desain pre eksperimen dengan pendekatan pre-posttest one group design. 32 responden dipilih secara purposif. Intervensi telenursing diberikan tiga kali selama satu minggu, dengan menggunakan media Whatsapp grup. Instrumen yang digunakan adalah lembar ceklis SDIDTK (Stimulasi Deteksi Intervensi Dini Tumbuh Kembang). Hasil: Hasil uji T berpasangan menunjukkan bahwa telenursing efektif dalam meningkatkan kemampuan ibu dalam melakukan stimulasi tumbuh kembang pada anak (p=0,000). Telenursing memungkinkan perawat untuk mengontrol pemberian intervensi keperawatan, meskipun tidak bertemu secara langsung. Simpulan: Telenursing dapat menjadi alternatif metode yang digunakan untuk memberikan asuhan keperawatan, salah satunya dalam memberikan informasi tentang tumbuh kembang anak.